Exercise interventions on body composition and quality of life of overweight/obese breast cancer survivors: a meta-analysis - Hongchang Yang; Li Liu; Xiaoxia Zhang (BMC Women's Health, 2023)
Abstract Background This meta-analysis aimed to assess the effects of exercise interventions on body composition and quality of life in overweight/obese breast cancer survivors. Methods Eligible randomized controlled trials (RCTs) were searched from the Cochrane Library, PubMed, and Embase databases and assessed using the Cochrane Collaboration’s assessing risk tool. The effect size was pooled as weighted mean difference (WMD) for body composition variables (i.e., body mass index [BMI], body fat, body weight, fat mass, lean mass, bone mineral density) and quality of life (i.e., physical health and mental health), and the confidence interval (CI) was set as 95%. Since heterogeneity existed, subgroup analysis was conducted to detect the source of heterogeneity. Results Eight articles from six RCTs containing 548 overweight/obese breast cancer survivors (BMI ≥ 25 kg/m2) were included and analyzed. Compared to routine care, exercise intervention significantly decreased the body mass index [WMD (95% CI) = -1.37 (-2.50, -0.23) kg/m2] and body fat [WMD (95% CI) = -3.80 (-6.59, -1.01) %] of overweight/obese breast cancer survivors. Exercise intervention showed a tendency to increase physical health [WMD (95% CI) = 2.65 (-10.19, 15.48)] and mental health [WMD (95%CI) = 1.38 (-4.18, 6.95)], but no statistical significance was observed. A subgroup analysis showed the duration of intervention was a source of heterogeneity on body composition. In the 16-week subgroup, exercise intervention decreased fat mass and BMI while increased lean mass and bone mineral density. The 52-week exercise intervention was effective in increasing lean mass. A significant exercise intervention effect on reducing body fat was only detected in the 12-week subgroup. Conclusion Exercise intervention significantly decreased the body mass index and body fat of overweight/obese breast cancer survivors. The benefits of exercise interventions for overweight/obese breast cancer survivors need more evidence from high-quality RCTs with large sample sizes.